Preparation Of 70% Ethanol Extract Of Pumpkin Nanoparticles (Sechia Edulle) Using The Inonic Gelation Method In Lozenges Tablet Formulation - Rindu Ananda Aprilia; Ni Putu Happy Ana Kristina; Alila Fingkita Sari; Rita Gustina; Anung Kustriyani (PROFESSIONAL HEALTH JOURNAL, 2025)
Introduction:Chayote is a plant that is efficacious in lowering blood pressure. High blood pressure in hypertension can cause increased morbidity and mortality. These bad effects can be avoided by taking medication regularly. The aim of taking medication regularly is to ensure that drug levels in the blood remain within the therapeutic range. Apart from that, to achieve maximum drug levels in the blood is to make the drug into nanoparticles. Objectives: The aim of this research is to prepare nanoparticles of 70% ethanol extract of Chayote using the ionic gelation method. Methods:The research method is laboratory experimental. The research data is in the form of quantitative data, namely the size of the nanoparticles. Results: Nanoparticle preparation was carried out using a solution of 1% Chitosan and 0.5% Na TPP with a ratio of 2:1. The results of nanoparticle preparation were tested using Particle Size Analysis. The yield weight of the extract was also calculated at 27.73%. The measurement results of 70% Chayote ethanol extract nanoparticles were 556,5 nm. Conclusions: the particle size meets the criteria for nanoparticles of 10-1000 nm (556,5 nm).